STRIDE—a fluorescence method for direct, specific in situ detection of individual single- or double-strand DNA breaks in fixed cells. Issue 3 (13th December 2019) - Kordon, Magdalena M; Zarębski, Mirosław; Solarczyk, Kamil; Ma, Hanhui; Pederson, Thoru; Dobrucki, Jurek W
Abstract: We here describe a technique termed STRIDE (SensiTive Recognition of Individual DNA Ends), which enables highly sensitive, specific, direct in situ detection of single- or double-strand DNA breaks (sSTRIDE or dSTRIDE), in nuclei of single cells, using fluorescence microscopy. The sensitivity of STRIDE was tested using a specially developed CRISPR/Cas9 DNA damage induction system, capable of inducing small clusters or individual single- or double-strand breaks. STRIDE exhibits significantly higher sensitivity and specificity of detection of DNA breaks than the commonly used terminal deoxynucleotidyl transferase dUTP nick-end labeling assay or methods based on monitoring of recruitment of repair proteins or histone modifications at the damage site (e.g. γH2AX). Even individual genome site-specific DNA double-strand cuts induced by CRISPR/Cas9, as well as individual single-strand DNA scissions induced by the nickase version of Cas9, can be detected by STRIDE and precisely localized within the cell nucleus. We further show that STRIDE can detect low-level spontaneous DNA damage, including age-related DNA lesions, DNA breaks induced by several agents (bleomycin, doxorubicin, topotecan, hydrogen peroxide, UV, photosensitized reactions) and fragmentation of DNA in human spermatozoa. The STRIDE methods are potentially useful in studies of mechanisms of DNA damage induction and repair in cell lines and primary cultures, including cells with impaired repair mechanisms.